Connections between trade policy and migration: A sphere of action for the EU - Evita Schmieg (Stiftung Wissenschaft und Politik (SWP), 2019)
Trade agreements can contribute to long term development - and thus to addressing the causes of flight and migration - as long as they consistently pursue sustainable development and real market opening. The latest theoretical and empirical findings highlight the enormous complexity of the relationship between trade and migration. Other factors (such as war, economic crisis etc.) often play a larger role as triggers of migration than trade policy and trade agreements. One aspect is incontestable: Migration always has a positive effect on trade flows. Conversely, the effect of trade agreements on migration is sometimes positive, sometimes negative: If they lead to increasing per capita income they may temporarily stimulate migration. A certain level of income is required before people are able to emigrate at all. Using trade agreements to create legal migration opportunities in the area of services reduces the incentive for irregular migration. This question is especially relevant for the EU, as it faces the looming problem of labour shortages in the ageing societies of its member states. Ecological and social aspects of investment and trade should be better integrated in all free trade agreements. South Africa and the countries of North Africa offer the greatest potential to expand market access. The EU has already completely opened its markets to most sub-Saharan countries. The respective policy instruments for trade and migration need to be better coordinated in order to reduce the contradictions between them and to address justified concerns about uncontrolled immigration.
Keywords: 320